Trade relations between the Song and Jin Empires: smuggling against embargo - Maria S. Kruglova (RUDN Journal of World History)
The growing socio-political interest to the northeastern territories of China in terms of the historical prerequisites for their economic and political connections with traditional China defines the scientific interest the article. The purpose of the presented study is to identify the main trade features between the Jurchen and the Chinese during the Song (960-1279) and Jin periods, with an emphasis on smuggling trade. The research literature mainly presents the political and military side of the relationship between the Song and Jin, emphasizing that trade between the two states was suppressed. However, trade played a fundamental role in the relations between the two empires. Due to the characteristics of the seminomadic economy, trade with neighboring states was one of the main conditions for the existence of the Jin Empire. The Jin Empire traded with its neighbors throughout its existence, but the Song Empire always remained its main trading partner. Based on such sources as Jin-shi, Song-shi and Song Huiyao Jigao, the main features of trade of the two empires, trade items, as well as factors that positively and negatively influenced trade relations between the two countries were identified. The main items of trade were horses, livestock products, tea, grain and salt. After the conquest of northern China by the Jin Empire and the beginning of its political confrontation with the Southern Song, the Southern Song government imposed a ban on trade with the Jurchens. The restrictions introduced stimulated the transition to mechanisms of informal trade exchange, and the role of smuggling transactions increased significantly.